Biostratigraphy of Hartha Formation from Selected Wells in Nasiriyah Oil Field, Southern Iraq - Mousa, Anwar K.; Shakir, Luay S. (Iraqi Journal of Science, 2023)
The Hartha Formation has been investigated from a biostratigraphic view in three subsurface sections in the Nasiriyah Oil field, wells Ns1, Ns3, and Ns4, South of Iraq. Hartha Formation is composed of limestone and has various areas of intense dolomitization alternating with marly limestone. The formation ranges in thickness from 126 to 182 meters. Thirteen large and small benthic foraminifer species and genera are identified from Hartha Formation. Based on the large benthic foraminifer's assemblage, one distinct biozone was recognized after an examination of the paleontological datum in the investigated area showed that the studied wells contained a diversity of foraminiferal species, the larger foraminifers biozone was proposed: Orbitoides medius- Orbitoides tissoti - Orbitoides gensacicus -Orbitoides apiculatus - Omphalocyclus macroporus assemblage zone (Late Campanian- Early Maastrichtian), this biozone divided in two range subzone: Orbitoides medius Partial Range Zone (Late Campanian) and Omphalocyclus macroporus Range Zone (Early Maastrichtian). This biozone indicated that the Hartha Formation deposited through (Late Campanian- Early Maastrichtian).